2023
DOI: 10.1021/acs.jmedchem.3c00872
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Triazolyl Derivatives of Cucurbitacin B Targeting IGF2BP1 against Non-Small Cell Lung Cancer

Fan-Fan Shang,
Qing Lu,
Tailiang Lin
et al.

Abstract: Cucurbitacin B (CuB) is a potent but toxic anticancer natural product. Herein, we designed and synthesized 2-OH-and 16-OH-modified CuB derivatives to improve their antitumor efficacy and reduce toxicity. Among them, derivative A11 had the most potent antiproliferative activity against A549 lung cancer cells (IC 50 = 0.009 μM) and was approximately 10-fold more potent than CuB, while the cytotoxicity of A11 toward normal L02 cells was about 10-fold less potent, indicating a much wider therapeutic window than Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The high presence of M2-like TAMs is associated with osteosarcoma metastasis and indicates poor prognosis (Alzahrani, 2019). CuB inhibits tumour growth in multiple cancers (Chan et al, 2010;Ge et al, 2018;Huang et al, 2023;Liu, Li, et al, 2022;Shang et al, 2023;Zhang et al, 2022). Before investigating the mechanistic actions of CuB on M2 macrophages, it is important to highlight the basis of our experimental concentration selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high presence of M2-like TAMs is associated with osteosarcoma metastasis and indicates poor prognosis (Alzahrani, 2019). CuB inhibits tumour growth in multiple cancers (Chan et al, 2010;Ge et al, 2018;Huang et al, 2023;Liu, Li, et al, 2022;Shang et al, 2023;Zhang et al, 2022). Before investigating the mechanistic actions of CuB on M2 macrophages, it is important to highlight the basis of our experimental concentration selection.…”
Section: Discussionmentioning
confidence: 99%
“…CuB's potent anti-inflammatory and anticancer activities have made it a focal point in cancer research (Chen et al, 2005). Specifically, in cancers including lung (Liu, Li, et al, 2022;Shang et al, 2023), colorectal (Huang et al, 2023;Zhang et al, 2022) and hepatocellular carcinomas (Chan et al, 2010;Ge et al, 2018), CuB has shown the potential to inhibit tumour cell activities through diverse mechanisms, including signalling pathway inhibition (Liu, Li, et al, 2022) and cell cycle arrest (Chan et al, 2010). Additionally, CuB's effects have been noted in other cancers, including breast cancer, prostate cancer and osteosarcoma, amongst others (Alafnan et al, 2022(Alafnan et al, , 2023Garg et al, 2020;Jin et al, 2018;Liang et al, 2019;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%